2022
DOI: 10.1038/s41586-022-05231-w
|View full text |Cite
|
Sign up to set email alerts
|

A wheat resistosome defines common principles of immune receptor channels

Abstract: Plant intracellular nucleotide-binding leucine-rich repeat receptors (NLRs) detect pathogen effectors to trigger immune responses1. Indirect recognition of a pathogen effector by the dicotyledonous Arabidopsis thaliana coiled-coil domain containing NLR (CNL) ZAR1 induces the formation of a large hetero-oligomeric protein complex, termed the ZAR1 resistosome, which functions as a calcium channel required for ZAR1-mediated immunity2–4. Whether the resistosome and channel activities are conserved among plant CNLs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
214
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(226 citation statements)
references
References 68 publications
11
214
0
1
Order By: Relevance
“…Fungal and metazoan N-terminal 4 helix bundle domains cause cell death in an analogous fashion to plant CC domains 12,[46][47][48] . Intriguingly, CC domain mechanisms may be widely transferable between kingdoms as cell death was reported in metazoan cells expressing angiosperm CC-NLRs 18,19 . While this remains to be explored in further detail, these findings suggest that fundamental biochemical mechanisms may underpin the function of CC-like 4 helix bundles across the tree of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal and metazoan N-terminal 4 helix bundle domains cause cell death in an analogous fashion to plant CC domains 12,[46][47][48] . Intriguingly, CC domain mechanisms may be widely transferable between kingdoms as cell death was reported in metazoan cells expressing angiosperm CC-NLRs 18,19 . While this remains to be explored in further detail, these findings suggest that fundamental biochemical mechanisms may underpin the function of CC-like 4 helix bundles across the tree of life.…”
Section: Discussionmentioning
confidence: 99%
“…Upon pathogen virulence factor-dependent activation, the Arabidopsis CC-NLR receptor ZAR1 (hopZ1-Activated Resistance1) forms higher order oligomer complexes ('resistosome') in which the primary helix of each CC domain 4-helix bundle assembles into a funnel-shaped structure predicted to form pores within the plasma membrane 15,16 . In support of this idea, activated Arabidopsis ZAR1 or wheat Sr35 (Stem rust resistance 35) pentamers were shown to accumulate at lipid bilayers and act as non-selective cation channels in vitro 17,18 . This paradigm was further confirmed for the CCRPW8 domains of Arabidopsis NRG1 and ADR1, which exhibited oligomerization-dependent ion channel activity requiring the N-terminal region of the CCRPW8 domain 19 .…”
mentioning
confidence: 92%
“…In all four hvNLR clades we observed that the surface of the LRR domains contained a cluster of variable residues (Figure 3). This pattern of sequence variation suggests a direct recognition mechanism similar to that of RPP1, Roq1, and Sr35, the direct-recognition NLRs with structures presently available in the PDB (Zhao et al, 2022;Martin et al, 2020;Ma et al, 2020;Förderer et al, 2022). In the Int3480 clade, there were two such clusters on the opposite side of the LRR horseshoe that both faced the central cavity, suggesting a bipartite binding site in this receptor (Figure 3A).…”
Section: Resultsmentioning
confidence: 84%
“…These specificity-determining residues characteristically cluster on the concave side of the LRR domain. Targeted modification of these residues might lead to derivation of novel immune specificities in the native maize NLRs, as demonstrated for wheat disease resistance genes Sr33, Sr50 (Tamborski et al, 2022), and Sr35 (Förderer et al, 2022) thus overcoming the relative lack of natural diversity. Despite the differences in exact positions of the candidate binding residues among hvNLRs, our results agree with the inference by Förderer et al that target binding on the inside of the LRR favors an open NB-ARC conformation in an activation mechanism shared among distantly related direct-recognition NLRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation